o termo geral da sequência (2,3,4,5,6...)
Soluções para a tarefa
Respondido por
21
a1 = 2
a2 = 3
r = a2 - a1 = 3 - 2 = 1
an = a1 + (n - 1).r
an = 2 + (n - 1).1
an = 2 + n - 1
an = 1 + n
Resposta: an = 1 + n
Espero ter ajudado.
a2 = 3
r = a2 - a1 = 3 - 2 = 1
an = a1 + (n - 1).r
an = 2 + (n - 1).1
an = 2 + n - 1
an = 1 + n
Resposta: an = 1 + n
Espero ter ajudado.
Perguntas interessantes
Química,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás